Mencermati Demokratisasi dalam Proses Kepengurusan Partai Politik di Indonesia - Dewi, Kaamiliaa; Nurmandi, Achmad; Fridayani, Helen Dian (Jurusan Ilmu Politik Universitas Bangka Belitung, 2025)
This research aims to analyze the democratization process of political party management in Indonesia, focusing on recent democratic developments. Political parties play an important role in a democratic system, and the internal democratic leadership process within a party can reflect the overall quality of democracy. This research uses a qualitative method with data collection through documentation. The data collected is analyzed descriptively to describe the recent development of democratization of political party management in Indonesia. Research on political parties increasingly recognizes the importance of transparency and accountability. Political parties in Indonesia tend to focus on government power and ignore their own interests. Stricter control and accountability mechanisms have been implemented to reduce nepotism and corruption within parties. However, the management of political parties has not run optimally, this is characterized by conflicts of interest, weak coordination between government agencies, and technical constraints. This research still faces obstacles in obtaining secondary data related to the democratization of political parties. Therefore, it is important to involve analysis that considers aspects of long-term research. Feedback from readers is needed for future articles.